PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA KELAS X.E1 SMA NEGERI 6 DENPASAR TAHUN PELAJARAN 2023/2024 - I Komang Sukendra; I Wayan Pebri Muliatmika; I Wayan Suwiasa (Widyadari, 2024)
Various methods have been employed by teachers in school, but they have not yet achieved maximum results. Therefore, innovation in classroom learning is needed, one of which is the implementation of the Discovery Learning model. The aim of this research is to determine whether the implementation of the Discovery Learning model can enhance student learning activities in mathematics. This type of research is classroom action research (CAR). The subjects of this research were students of class X.E1 at SMA Negeri 6 Denpasar in the 2023/2024 academic year. The object of the research was the students' learning activities in mathematics on the topic of Statistics with the application of the Discovery Learning model. This classroom action research was carried out in two cycles, which included initial reflection, action planning, action implementation, observation/data collection, and reflection. Data collection was done through observation. The instrument used was an observation sheet related to student learning activities. The data analysis technique used was descriptive analysis. Based on the results of the action research, it was shown that the application of the Discovery Learning model can enhance student learning activities in mathematics on the topic of Statistics for class X.E1 students at SMA Negeri 6 Denpasar in the 2023/2024 academic year. With the average completeness of student learning activities in cycle I being 73.81% and increasing to 83.53% in cycle II.